On the Monte Carlo simulation of small-field micro-diamond detectors for megavoltage photon dosimetry - Andreo, Pedro; Palmans, Hugo; Marteinsdóttir, Maria; Benmakhlouf, Hamza; Carlsson-Tedgren, Åsa (Physics in medicine & biology, 2016)
Monte Carlo (MC) calculated detector-specific output correction factors for small photon beam dosimetry are commonly used in clinical practice. The technique, with a geometry description based on manufacturer blueprints, offers certain advantages over experimentally determined values but is not free of weaknesses. Independent MC calculations of output correction factors for a PTW-60019 micro-diamond detector were made using the EGSnrc and PENELOPE systems. Compared with published experimental data the MC results showed substantial disagreement for the smallest field size simulated ( mm). To explain the difference between the two datasets, a detector was imaged with x rays searching for possible anomalies in the detector construction or details not included in the blueprints. A discrepancy between the dimension stated in the blueprints for the active detector area and that estimated from the electrical contact seen in the x-ray image was observed. Calculations were repeated using the estimate of a smaller volume, leading to results in excellent agreement with the experimental data. MC users should become aware of the potential differences between the design blueprints of a detector and its manufacturer production, as they may differ substantially. The constraint is applicable to the simulation of any detector type. Comparison with experimental data should be used to reveal geometrical inconsistencies and details not included in technical drawings, in addition to the well-known QA procedure of detector x-ray imaging.